Analysis of a school feeding plan contract PAE state contracting - public bidding - contract 005-2023 (2023)
School feeding is one of the most important factors for development during the school years. For this reason, the state of Colombia launched a school feeding program, the program is regulated by the Ministry of National Education (MEN), which establishes the parameters that each territorial entity must take into account when implementing the program that must be contemplated in the Departmental and municipal development plans. Therefore, to implement the program, the state implements it through public contracts through various contract modalities. For the execution of the School Feeding Plan of the Department of Antioquia in the municipality of Turbo, it was developed through public bidding where the state entity, the District Mayor's Office of Turbo, carried out a public contest in which the interested parties have equal opportunities to present their offers and the companies awarded the contracts to the most appropriate proposals, leaving LA UNIÓN TEMPORAL UT TURBO E23 in charge of the development of school feeding in the municipality of Turbo, where the execution of the current year was carried out.